Analysis of Audience Reception of Sexual Violence in Copying Light Film - Agusty, Mayang Firmanda; Aisha, Vinisa Nurul (Universitas Muhammadiyah Surakarta, 2022)
Purpose: The purpose of this study is to understand the reception depicted by the audience about violence sex that happened in the Copying Light film. This study uses the reception theory by Stuart Hall. Methodology: This study uses qualitative method and as for the data collecting process, this study uses interview as the method. Results: The result of this study shows that there are three informants in the dominant position and two informants in the negotiated position.